Experimental substantiation of the effective mode of infrared radiation exposure on human body during infrared therapy - A. V. Vorobey; A. N. Osipov; M. H-M. Thostov; I. A. Telesh (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The authors developed an infrared (IR) cabin with biotechnical feedback, which solves the problems of increasing the efficiency and safety of IR heating procedure. The target audience for the developed IR cabin includes two groups: 1) young people who embrace an active lifestyle (using the IR cabin for health purposes); 2) mature and elderly people, including those with cardiovascular diseases (using the IR cabin for therapeutic purposes). The research conducted determines the effective mode of infrared radiation exposure to a human body. To assess the effectiveness of exposure the authors propose a coefficient equal to the ratio of weight loss of the user to the maximum operating temperature in the infrared cabin at body level. It is established that a person experiences effective heating at the working temperature of air inside the IR cabin (at body level) in the range from 40 to 42 °C. This temperature regime already contributes to intense sweating, but does not yet lead to discomfort and undesirable load on the cardiovascular system. The beginning of the IR heating should be considered the moment when the IR cabin reaches the operating temperature of 40 °C. Based on the monitoring of indicators of the thermal conditions of the IR cabin, it is necessary to automatically maintain the temperature range from 40 to 42 °C during IR heating. Control of the user's physiological parameters during IR therapy and automatic correction of the power of IR radiators will make the IR heating procedure safe for users. The developed IR cabin can be used in health resort and healthcare institutions of the Republic of Belarus.